Pengaruh Kapitalisasi Pasar Dan Good Corporate Governance Terhadap Pengungkapan Corporate Social Responsibility - Oktavila Oktavila; Erinos NR (Jurnal Eksplorasi Akuntansi, 2019)
The purpose of the research is to know the market capitalization, and the good corporate governance that is proxied by the institutional ownership, the audit committe, and the commissioner size. This study uses secondary data from the company’s annual report for 2015-2017. The sampling method in this study used purposive sampling with a sample of 63 manufacturing companies listed on the indonesia Stock Exchange in 2015-2017. The analysis used in this multiple linear regression analysis. The results showed that the market capitalization and commissioner size had a significant positive effect on corporate social responsibility disclosure, while the audit committe has a positive and insignificant effect on corporate social responsibility disclosure, and institutional ownership has significant negative effect on corporate social responsibility disclosure.